GENETIC VARIATION AND RELATEDNESS AMONG HIGH YIELDING RICE VARIETIES (Oryza sativa L.) REVEALED BY RAPD MARKERS (Bangladesh Journal of Plant Breeding and Genetics, 2008)
Genetic variation is a principal concern for the plant breeders. Genetic variation and relationship among high yielding rice varieties viz. Binadhan 4, Binadhan 5, Binadhan 6, Binasail, BRRI dhan28 and BRRI dhan29 were analyzed using four decamer random primers. Polymerase Chain Reaction (PCR) amplified 22 RAPD markers, of which 18 (81.82%) were polymorphic. The proportion of polymorphic loci and the gene diversity values were 59.09% and 0.25 for the Binadhan 4; 59.09% and 0.21 for Binadhan 6; 54.55% and 0.23 for Binasail; 54.55% and 0.19 for BRRI dhan29; 50.00% and 0.19 for Binadhan 5 and 45.45% and 0.18 for BRRI dhan28, respectively. The coefficient of gene differentiation (Gst) across all loci was calculated as 0.35 reflecting the existence of high level of genetic variation among the six modern rice varieties. UPGMA dendrogram based on Neis genetic distance segregated the six high yielding rice varieties into two clusters: all four mutant varieties viz. Binadhan 4, Binadhan 5, Binadhan 6 and Binasail formed one cluster and two varieties of BRRI grown in boro season, BRRI dhan28 and BRRI dhan29 grouped together in another cluster. Among the mutants, two boro season varieties, developed from the same parent, Binadhan 5 and Binadhan 6 grouped together with genetic distance of 0.10. Therefore, RAPD offer a reliable method to evaluate genetic variation and relatedness among the high yielding rice varieties.DOI: http://dx.doi.org/10.3329/bjpbg.v21i1.17042